Strategi Humas LLDIKTI Wilayah IV dalam Mengelola Konten Media Sosial Instagram - Puja Kharisma Nurfauziah Puja; Shopia Novita (Bandung Conference Series: Public Relations, 2023)
Abstract. The Certified Internship Program is one of the Independent Campus programs carried out by the Ministry of Education and Culture with the aim of providing opportunities for all students to develop their potential through activities outside the classroom. Through this program, Region IV Higher Education Service Institutions provide internship opportunities through several departments, one of which is Public Relations. In this case, the author as an intern occupies the position of Public Relations. Public relations utilizes information media as an intermediary for disseminating information within the scope of educational institutions. The purpose of this report is to find out how to plan to manage Instagram social media content carried out by Public Relations. In addition, it is also to find out the utilization of LLDIKTI Region IV information media in terms of messages and usability. The results of the final report of the Certified Internship program include that the Public Relations Strategy in managing Instagram social media is quite effective. The strategies undertaken include strategies from planning to management stages, monitoring social media strategies and strategies for utilizing Instagram social media content in terms of messages and usability. Abstrak. Program Magang Studi Independen Bersertifikat merupakan salah satu program Kampus Merdeka yang diusung oleh Kemendikbudristek dengan tujuan memberikan kesempatan kepada seluruh mahasiswa untuk mengembangkan potensi diri melalui aktivitas di luar kelas pembelajaran. Melalui program tersebut, Lembaga Layanan Pendidikan Tinggi Wilayah IV memberikan kesempatan magang melalui beberapa department yang ditawarkan, salah satunya yaitu Hubungan Masyarakat. Metode Penelitian ini menggunakan gjenis penelitian kualitatif dengan metode atau pendekatan studi kasus. Tujuan dari penelitian ini, untuk mengetahui bagaimana perencanaan hingga pengelolaan konten media sosial instagram yang dilakukan oleh Hubungan Masyarakat. Selain itu juga untuk mengetahui pemanfaatan media informasi LLDIKTI Wilayah IV dari segi pesan dan kegunaan. Untuk hasil penelitiannya ini meliputi bahwa strategi hubungam masyarakat dalam mengelola media sosial instagram sudah terbilang cukup efektif. Strategi yang dilakukan diantaranya terdiri dari strategi tahapan perencanaan hingga pengelolaan, strategi media sosial monitoring dan strategi dari pemanfaatan konten media sosial instagram dari segi pesan dan kegunaan.